(untitled) (American Journal of Islam and Society, 2024)
This article critically examines three authoritative Islamic discourses on political loyalty produced by prominent figures of Sunni reformist Islam: The Egyptian-Qatari Yūsuf al-Qaraḍāwī (1926-2022), the Mauritanian ʿAbdallāh b. Bayyah (b. 1935), and the Iraqi-Qatari ʿAlī al-Qaradāghī (b. 1949). First, I analyze the key arguments presented in each discourse: al-Qaradāghī advocates that allegiance is determined by fairness, whereas al-Qaraḍāwī retains a realist perspective on loyalty in context, while ʿAbdallāh b. Bayyah argues for a complementary relationship between loyalty to religion and to the homeland. Second, I discuss the three discourses in terms of the foundations, manifestations, and implications for political loyalty. Finally, I point out some of the limitations of the reformist notion of political loyalty toward non-Muslims, particularly in pluralist societies.